Between medieval men male friendship and desire in early medieval English literature - Clark, David, 1977- (Oxford : Oxford University Press, 2009)
This is a study of same-sex relations (both erotic and non-erotic) in the Anglo-Saxon period. David Clark's nuanced approach to gender and sexuality seeks to step outside modern cultural assumptions in order to explore the diversity and complexity that he shows to be characteristic of the period.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Male friendship in literature; Desire in literature; Eroticism in literature; Men in literature